A Sustainable & Biologically Inspired Prosthetic Hand for Healthcare - Secco, E. L.; Moutschen, C.; Agidew, T. F.; Nagar, A. K. (EAI Endorsed Transactions on Pervasive Health and Technology, 2018)
There are many persons in the world affected by amputation. Upper limb amputations require high cost prosthetic devices in order to provide significant motor recovery. We propose a sustainable design and control of a new anthropomorphic prosthetic hand: all components are modular and exchangeable and they can be assembled by non-expert users. Phalanges & articulations of the fingers and the palm are manufactured via a 3D printing process in Acrylonitrile Butadiene Styrene (ABS) or Polyactic Acid (PLA) materials. The design is optimized in order to provide human-like motion and grasping taxonomy through linear actuators and flexion tendon mechanisms, which are embedded within the palm. HardWare (HW) and Software (SW) open sourced units for ElectroMyography (EMG) input and control can be combined with a user-friendly and intuitive Graphical User Interface (GUI) to enable amputees handling the prosthesis. To reduce the environmental impact of the device lifetime cycle, the material and energy consumption were optimized by adopting: simple design & manufacturing, high dexterity, open source HW and SW, low cost components, anthropomorphic design.
Keywords: smart prosthetics; human-centred healthcare; sustainability; bio-mimetic